International Practice Variability in Treatment of Aneurysmal Subarachnoid Hemorrhage - Winkel, Jordi de; van der Jagt, Mathieu; Lingsma, Hester F.; Roozenbeek, Bob; Calvillo, Eusebia; Chou, Sherry H.-Y.; Dziedzic, Peter H.; Etminan, Nima; Huang, Judy; Ko, Nerissa U.; Loch MacDonald, Robert; Martin, Renee L.; et al. (Journal of Clinical Medicine, 2021)
Prior research suggests substantial between-center differences in functional outcome following aneurysmal subarachnoid hemorrhage (aSAH). One hypothesis is that these differences are due to practice variability. To characterize practice variability, we sent a survey to 230 centers, of which 145 (63%) responded. Survey respondents indicated that an estimated 65% of ruptured aneurysms were treated endovascularly. Sixty-five percent of aneurysms were treated within 24 h of symptom onset, 18% within 24-48 h, and eight percent within 48-72 h. Centers in the United States (US) and Europe (EU) treat aneurysms more often endovascularly (72% and 70% vs. 51%, respectively, US vs. other p < 0.001, and EU vs. other p < 0.01) and more often within 24 h (77% and 64% vs. 46%, respectively, US vs. other p < 0.001, EU vs. other p < 0.01) compared to other centers. Most centers aim for euvolemia (96%) by administrating intravenous fluids to 0 (53%) or +500 mL/day (41%) net fluid balance. Induced hypertension is more often used in US centers (100%) than in EU (87%, p < 0.05) and other centers (81%, p < 0.05), and endovascular therapies for cerebral vasospasm are used more often in US centers than in other centers (91% and 60%, respectively, p < 0.05). We observed significant practice variability in aSAH treatment worldwide. Future comparative effectiveness research studies are needed to investigate how practice variation leads to differences in functional outcome.